Alchemy and Chemical Medicines in Early Colonial Lima, Peru. (2nd April 2020) - Newson, Linda A.
Abstract : The article explores the use of minerals and the nature of chemical methods employed in Lima in the sixteenth and early seventeenth centuries. It does so through examining the availability of mineral resources, including pre-European knowledge of their use, through surveying the books and equipment used by physicians and apothecaries, and finally by examining prescriptions for medicines that were used to treat patients. It concludes that minerals were probably more commonly employed in medicines in Lima than in Spain but suggests that their preparation and use at this time drew on Spain's alchemical tradition rather than on writings by Paracelsus and his followers. It argues that this did not reflect the effectiveness of censorship by the Inquisition.